1989
DOI: 10.1177/036354658901700314
|View full text |Cite
|
Sign up to set email alerts
|

An organ culture model for assaying wound repair of the fibrocartilaginous knee joint meniscus

Abstract: We describe an in vitro organ culture system that can be used to test the effect of various substances and compounds on the wound healing process in the fibrocartilaginous substance of the knee joint meniscus. Using culture medium containing either 10% fetal bovine serum (FBS) or our recently developed serum-free, defined culture medium (DM), we have demonstrated the ability of meniscal fibrochondrocytes from intact rabbit menisci to extricate themselves from their surrounding matrix and migrate into an exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 20 publications
(4 reference statements)
2
38
0
1
Order By: Relevance
“…While the results described above demonstrate the promise of a cellularized, highly porous, aligned nanofibrous scaffold for meniscus repair, there remain additional considerations that should be addressed as this technology moves toward in vivo, clinical translation. For example, while the concentric explant model has been used extensively to assess integration, 20,36,37 it does not test the most physiologically relevant forces experienced by the meniscus or the clinical scenario of replacement. Implanted engineered meniscus scaffolds will be exposed to simultaneous compressive forces and tensile forces, rather than the shear forces that arise in the push-out testing modality.…”
Section: Discussionmentioning
confidence: 99%
“…While the results described above demonstrate the promise of a cellularized, highly porous, aligned nanofibrous scaffold for meniscus repair, there remain additional considerations that should be addressed as this technology moves toward in vivo, clinical translation. For example, while the concentric explant model has been used extensively to assess integration, 20,36,37 it does not test the most physiologically relevant forces experienced by the meniscus or the clinical scenario of replacement. Implanted engineered meniscus scaffolds will be exposed to simultaneous compressive forces and tensile forces, rather than the shear forces that arise in the push-out testing modality.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro culture system, meniscus fibrochondrocytes have been shown to be capable of extricating themselves from their surrounding matrix and migrating into a purified fibrin clot. 42 In vivo studies have also shown the efficacy of an exogenous fibrin clot to support a repair response in the avascular portion of the meniscus. 14,22 Therefore, fibrin can be considered a quintessential model for the matrices on which tissue-engineered menisci are created; it provides a deformable scaffold for even cell distribution, migration, and orientation, and the ability to degrade over time.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to promote healing in the avascular region of the meniscus, Arnoczky et al (4) demonstrated in vivo that, when meniscal defects in this region are filled with a fibrin clot, a fibrocartilage repair tissue is generated. With an in vitro model, Webber et al (16) demonstrated that a fibrin clot filled defect would heal only partially; this suggested that factors other than the fibrin clot itself are required for effective healing.…”
Section: Discussionmentioning
confidence: 99%